The Influence of the Competence Component of Intellectual Capital and Financial Efficiency on the Capitalization of Russian Manufacturing Companies - Yu. Yu. Savchenko (Финансы: теория и практика, 2023)
The object of the study is Russian industrial companies whose shares are traded on the Moscow Exchange. The study’s subject is financial and financial connections in the field of using intellectual capital’s competence component as an important factor in business growth. The relevance of the study is important for the increasing role of intellectual capital and its components as a determining factor in business growth, as well as the need to identify new determinants that influence company capitalization. In the context of overcoming the consequences of sanctions, intellectualization and digitalization of the economy, the problem of the study of the dependency of the capitalization of Russian companies on the state of the components of intellectual capital is significantly updated. The purpose of the study is to assess and model the impact of the competence component of intellectual capital and financial efficiency on the capitalization of Russian manufacturing companies.Methods of comparative and statistical analysis, calculation of financial and economic indicators, correlation and regression analysis, and the Farrar-Glauber test were used. According to correlation analysis, the capitalization of Russian public companies in the production sector is influenced by an internal factor such as patent activity. The constructed multifactor linear regression model allows for the conclusion that a 1% increase in the number of patents raises the company’s market capitalization by 1.23% while all other factors remain constant. It is concluded that in the Russian market the importance of material assets as a factor in business growth significantly prevails over the influence of the competence component of intellectual capital. Recommendations are given, the implementation of which in the practice of Russian manufacturing companies will maximize their capitalization by taking into account the financial and economic advantages from the use of the competence component of intellectual capital.